Sources of Journalism Theory. Milton’s Areopagitica in Bulgaria - Osikovski, Martin (Research Papers, 2014)
Literary and journalism historians traditionally consider John Milton’s famousAreopagitica to be the first systematic defense of the liberty of the press. The Bulgarian reception of this important text is, however, only very scarce. This paper discusses the episodic contributions of Bulgarian scholars in this regard – starting from 1921, when a local political newspaper published the first Bulgarian translation of a minor section ofAreopagitica, and ending with some contemporary studies of history and theory of journalism. As an appendix, the text offers a commented Bulgarian translation of a longer section ofAreopagitica in which Milton examined in detail the historical evolution of licensed printing.
Keywords: Milton; Areopagitica; Liberty of press; Freedom of speech; Censorship